Peran Ukuran Bank Memoderasi Pengaruh Faktor Internal Bank terhadap Penyaluran Pembiayaan Bank Umum Syariah di Indonesia - Lida Vania Noviantie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
As a financial intermediation, one of the main activities of Islamic banking is the distribution of bank financing. Bank financing is the largest contributor to the asset portfolio and represents a key source of the bank’s operating revenue. The purpose of this study is to analyze the internal bank factors that influence bank financing, such as the Capital Adequacy Ratio (CAR), Return on Assets (ROA), Liquidity and Non-Performing Financing (NPF), with Bank Size as a moderating variable. The population of this study consists of Islamic Commercial Banks (BUS) in Indonesia during the period 2019–2024, and by using purposive sampling, a total of 11 banks were obtained as the research sample. The data used are secondary data derived from the financial statements of each bank. The research methodology applied is Moderated Regression Analysis (MRA) using EViews 13. The results of this study indicate that the CAR variable has a negative but insignificant effect on bank financing, while the ROA, Liquidity, and NPF variables have a significant negative effect on bank financing. Furthermore, bank size can moderate the effect of ROA, Liquidity, and NPF on financing distribution; however, bank size cannot moderate the effect of CAR on financing distribution.